2007
DOI: 10.1007/s11104-007-9382-6
|View full text |Cite
|
Sign up to set email alerts
|

N2O emission from soil following combined application of fertiliser-N and ground weed residues

Abstract: Emissions of N 2 O and CO 2 were measured following combined applications of 15 N-labelled fertiliser (100 μg N g −1 ; 10 atom % excess 15 N) and organic olive crop weed residues (Avena sativa, Ononis viscosa, Ridolfia segetum and Olea europea; 100 μg N g −1 ) to a silt loam soil under controlled environment conditions. The objective was to determine the effect of varying combinations of inorganic fertiliser and plant residues on these emissions and soil mineral N dynamics. Emissions were generally increased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 32 publications
1
55
1
3
Order By: Relevance
“…N 2 O emission from soils amended with crop residue has often been reported to be influenced by initial N content, C:N ratio, lignin content, polyphenol content, and lignin:N ratio, polyphenol:N ratio or (lignin ? polyphenol):N ratio (Constantinides and Fownes 1994;Garcia-Ruiz and Baggs 2007;Palm and Rowland 1997). In this experiment, however, the lignin and extractable polyphenol contents of the cowpea and maize residues were lower than the 15% lignin and 3-4% polyphenol threshold levels proposed in the Organic Resources Database (Palm et al 2001) and by other authors (Constantinides and Fownes 1994;Palm et al 2002;Palm and Rowland 1997) to retard residue N mineralization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N 2 O emission from soils amended with crop residue has often been reported to be influenced by initial N content, C:N ratio, lignin content, polyphenol content, and lignin:N ratio, polyphenol:N ratio or (lignin ? polyphenol):N ratio (Constantinides and Fownes 1994;Garcia-Ruiz and Baggs 2007;Palm and Rowland 1997). In this experiment, however, the lignin and extractable polyphenol contents of the cowpea and maize residues were lower than the 15% lignin and 3-4% polyphenol threshold levels proposed in the Organic Resources Database (Palm et al 2001) and by other authors (Constantinides and Fownes 1994;Palm et al 2002;Palm and Rowland 1997) to retard residue N mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Gas sampling and analysis were done following the procedures described in and Garcia-Ruiz and Baggs (2007). Gas samples for N 2 O and CO 2 analysis were collected from the Kilner jar headspaces on day 0, (6 h after addition of fertiliser and residues), and on days 1, 2, 3, 5, 7, 10, 14 and 30 after addition.…”
Section: Gas Sampling and Analysismentioning
confidence: 99%
“…Gaseous N losses are not only important in terms of the absolute N losses from the Nutr Cycl Agroecosyst (2009) 84:179-202 193 cropping system, compared for example to the total productive N losses (Table 6), but also, due to ammonia volatilization and denitrification, the most limiting fraction of N in organic farming systems, the readily available inorganic-N, was lost. Any gaseous N loss has a double negative effect: it reduces the absolute amounts of available N, and it reduces simultaneously the N availability of the organic N remaining in the manure, as the N availability in organic manures also depends on their total N concentration (Kyvsgaard et al 2000;Garcia-Ruiz and Baggs 2007). For example, in FYM 380 kg N were lost due to gaseous N losses.…”
Section: N Outputsmentioning
confidence: 99%
“…With regard to the crop residue characteristics, the most important property is its C/N ratio that determines organic N dynamics in the soil (Heal et al 1997;Baggs et al 2003;Al-Kaisi and Yin 2005;Garcia-Ruiz and Baggs 2007). In particular, it has been shown that higher N 2 O emissions occur from soil after the incorporation of residues with low C/N ratio, such as legumes, rather than after cereal straw as a result of mineralization processes (Baggs et al 2000;Huang et al 2004;Raiesi 2006).…”
Section: Introductionmentioning
confidence: 99%